2019
DOI: 10.1158/1078-0432.ccr-18-1480
|View full text |Cite
|
Sign up to set email alerts
|

DNA Sequencing of Small Bowel Adenocarcinomas Identifies Targetable Recurrent Mutations in the ERBB2 Signaling Pathway

Abstract: Purpose: Little is known about the genetic alterations characteristic of small bowel adenocarcinoma (SBA). Our purpose was to identify targetable alterations and develop experimental models of this disease. Experimental Design: Whole-exome sequencing (WES) was completed on 17 SBA patient samples and targeted-exome sequencing (TES) on 27 samples to confirm relevant driver mutations. Two SBA models with ERBB2 kinase activating mutations were tested for sensitivity to anti-ERBB2 agents in vivo and in vitro. Bioch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 43 publications
1
41
3
Order By: Relevance
“…By contrast, genetic analyses of SBAs, including nonampullary DAs, have been performed by multiple groups [17][18][19][20][21][22][23]. Schrock et al [20] analyzed mutations of cancer-related genes in 317 SBA samples and showed that the genetic signatures of SBAs were distinct from those in CRCs or gastric cancers.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, genetic analyses of SBAs, including nonampullary DAs, have been performed by multiple groups [17][18][19][20][21][22][23]. Schrock et al [20] analyzed mutations of cancer-related genes in 317 SBA samples and showed that the genetic signatures of SBAs were distinct from those in CRCs or gastric cancers.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally believed that dysregulated ERBB2 signaling plays a key role in the development of pancreatic cancer (Lin et al, 2019). For the treatment of intestinal adenocarcinoma, ERBB2 mutations and amplification in small intestinal adenocarcinoma patients also make a great contribution (Adam et al, 2019). Recent studies have shown that HER2 targeted therapy has significantly improved outcomes in patients with breast and stomach problems with ERBB2 mutation/amplification (Meric-Bernstam et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the mutation rate of APC is markedly higher in CRC than in small intestine adenocarcinoma [ 148 ]. Nevertheless, some inactive variants of Wnt repressors RNF43 and ZNRF3 could lead to the activation of this pathway in other intestinal tumors [ 187 ].…”
Section: Balance Between Pro-apoptotic and Pro-survival Factors (Mmentioning
confidence: 99%